Ferula communis leaf extract: antioxidant capacity, UHPLC–MS/MS analysis, and in vivo and in silico toxicity investigations - Ed-Dahmani, Imad; El Fadili, Mohamed; Nouioura, Ghizlane; Kandsi, Fahd; Atki, Yassine El; Abuelizz, Hatem A.; Conte, Raffaele; Zahra Lafdil, Fatima; Taleb, Abdeslam; Abdellaoui, Abdelfattah; Taleb, Mustapha (Frontiers in Chemistry, 2025)
IntroductionFerula communis has demonstrated an abundance of pharmacological and antioxidative qualities.MethodsThis study investigates the antioxidant activity of F. communis leaf aqueous extract, total polyphenol and flavonoid concentrations, and ultra-high-performance liquid chromatography (UHPLC) composition and then evaluates the toxicity of the plant’s leaves in vitro and in silico. The major compound of the studied extract, namely, p-hydroxybenzoic acid, was chosen for a molecular docking technique to discover the inhibition mechanism toward antioxidant proteins. In addition, a detailed molecular dynamics simulation was carried out to examine the thermodynamic stability of the produced intermolecular interactions. The antioxidant capacity of the extracts of F. communis was evaluated using 2,2-diphenylpicryl hydroxyl (DPPH) radical and ferric reducing antioxidant power (FRAP) procedures. Acute toxicity was tested on albino mice at doses of 200, 300, and 400 mg/kg.ResultsThe results show that the polyphenol and flavonoid contents of the extract are significant (0.257 ± 0.003 mg Eq AG/mg and 0.32 ± 0.04 mg Eq Q/mg, respectively). The antioxidant activity illustrates that the extracts have notable activity in DPPH and FRAP assays. The toxicity study revealed that the mice’s behavior, body weight, and organ weights (liver and kidneys) were unaffected by Ferula communis leaf extract administration compared to controls. UHPLC–tandem mass spectrometry (MS/MS) analysis of the extract highlights the presence of 11 compounds, the most abundant of which is p-hydroxybenzoic acid, representing 53.65%. The predicted pharmacokinetic characteristics of absorption, distribution, metabolism, excretion, and toxicity (ADMET) attest to the well-absorbed nature of the isolated compounds, with human intestinal absorption (HIA) varying from 42% for arbutin (M3) to 100% for ursolic acid (M4).ConclusionIn conclusion, the leaves of Ferula communis are a good source of natural antioxidants and phenolic compounds. Thus, this study demonstrates that this plant has a wide range of applications, including natural food preservatives, pharmaceuticals, and cosmetics, as evidenced by ongoing research.